Himpunan Dominasi Ganda pada Graf Korona dan Graf Produk Leksikografi Dua Buah Graf - Fikri Maulana (Jurnal Matematika, 2016)
ABSTARCT. Let  be a subset of , with  is a graph without isolated vertices. A subset  of  referred to double domination in  if every vertex ,         such that every vertex in  minimal adjacent with two element of . The minimum cardinality of domination set, total domination set, and double domination set in  respectively is a is a domination number, total domination number, and double domination number denote respectively , , and . A double domination number in  minimum is two and a double domination number in  will not be more order () in , that .  A domination number if add one vertex of domination in  then the element of dimination number will not be more a double domination number in , that . In this final project examined the sum of bound of  doubel domination number in Corona and product lexicographic of two graphs. The minimum cardinality of double domination in Corona  is  with  is order in . Menwhile, the minimum cardinality of double domination in Product Lexicographic  at most .